2020
DOI: 10.1111/jace.17455
|View full text |Cite
|
Sign up to set email alerts
|

Room‐temperature bonding method of bioactive ultrathin glass film on titanium by a dissolution‐polymerization reaction

Abstract: Freestanding ultrathin glass film (UGF) of 45S5 bioglass was successfully bonded on a Ti substrate by the room-temperature bonding method. 45S5 UGFs with a thickness of 1~4 μm were fabricated by the glass-blowing technique, and the UGF was attached on the Ti plate at room temperature with a water layer between them. The bonding strength was about 370 mJ/m 2 just after bonding, and it increased during storing in the ambient atmosphere at room temperature and reached about 900 mJ/ m 2 after 9 hours storage. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(106 reference statements)
1
2
0
Order By: Relevance
“…This hypothesis is based on the role of basic catalysis in solvents for sol–gel synthesis 39,46,47 . A similar bonding mechanism based on this phenomenon has been proposed at the previous study of glass‐Ti bonding interface with Na 2 O‐rich layer and liquid water 48 . However, this reaction pathway is unlikely for our system where the amount of adsorbed water on the SiO 2 glass surface should be very small compared to liquid water 44 .…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This hypothesis is based on the role of basic catalysis in solvents for sol–gel synthesis 39,46,47 . A similar bonding mechanism based on this phenomenon has been proposed at the previous study of glass‐Ti bonding interface with Na 2 O‐rich layer and liquid water 48 . However, this reaction pathway is unlikely for our system where the amount of adsorbed water on the SiO 2 glass surface should be very small compared to liquid water 44 .…”
Section: Resultssupporting
confidence: 72%
“…39,46,47 A similar bonding mechanism based on this phenomenon has been proposed at the previous study of glass-Ti bonding interface with Na 2 O-rich layer and liquid water. 48 However, this reaction pathway is unlikely for our system where the amount of adsorbed water on the SiO 2 glass surface should be very small compared to liquid water. 44 Further, a reaction scheme via intra-surface proton transfer is also possible.…”
Section: Reaction Modelsmentioning
confidence: 91%
“…Among these applications, to improve its compatibility with the human body, especially bone bonding, many studies on modification and functionalization of the titanium surface have been reported continuously. [1][2][3][4][5][6][7] Regarding the abovementioned functionalization of titanium metal, several types of chemical treatment and electrical treatment related to TiO 2 formation are widely performed. However, most of these treatments are relatively complicated processes, for example, (a) hydrothermal reaction using strong acids and higher pressures 6 and (b) anodic oxidation using a higher voltage and strong acids.…”
Section: Introductionmentioning
confidence: 99%